The role of land records in support of post-conflict state buildingThe case of Rwanda - Todorovski D. (null, 2020)
Based on a case study conducted in Rwanda, firstly the type, the format and the status of land records are discovered, and then those are related with the process of post-conflict state building. This relation is explored in depth in order to determine and describe the role of land records in support of post-conflict state building. Here specific attention is paid to the role that land records have in land dispute resolution in such contexts. Findings from this paper shows that a strong relation exists and that land records play a positive role in support of the postconflict state building.